PURIFICATION, CLONING AND EXPRESSION OF SPINACH LEAF SUCROSE-PHOSPHATE SYNTHASE IN ESCHERICHIA-COLI - Sonnewald, Uwe; et al. (Planta, 1993)
Sucrose-phosphate synthase (SPS) from leaves of spinach (Spinacia oleracea L.) has been purified to homogeneity by a procedure involving precipitation with polyethylenglycol and chromatography over diethylaminoethylcellulose, OMEGA-aminohexylagarose, Mono Q and Blue Affinity columns. The purification factor was 838 and the final specific activity was 1.3 nkat . (mg protein)-1. On denaturing gels the major polypeptide was 120 kDa but there was also a variable amount of smaller polypeptides in the range of 90 to 110 kDa. A new activity stain was developed to allow visualization of SPS in gels. The holoenzyme had a molecular weight of about 240 and 480 kDa in native gels and Sepharose, respectively. A high-titre polyclonal antibody was obtained which reacted with SPS from other species including wheat, potato, banana and maize. Screening of a spinach-leaf cDNA-expression library with the antibody allowed the isolation of a full-length clone. Sequencing revealed a predicted molecular weight of 117649 Da, and considerable homology with the recently published sequence for maize leaf (Worrell et al. 1991, Plant Cell 3, 1121-1130). Expression of the spinach-leaf SPS gene in Escherichia coli resulted in biological activity, revealed by the presence of SPS activity in extracts and the accumulation of sucrose-6-phosphate and sucrose in the bacteria.
Keywords: CDNA CLONE (ENCODING SUCROSE-PHOSPHATE SYNTHASE); EXPRESSION (SPINACH SUCROSE-PHOSPHATE SYNTHASE IN ESCHERICHIA-COLI); NUCLEOTIDE SEQUENCE (SUCROSE-PHOSPHATE SYNTHASE); SPINACEA; SUCROSE-PHOSPHATE SYNTHASE (PURIFICATION; CLONING; EXPRESSION)